2002
DOI: 10.1046/j.1525-1497.2002.10629.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Brief Teaching Encounter Using Standardized Patients. Teaching Residents Alcohol Screening and Intervention

Abstract: OBJECTIVE: To investigate a brief teaching intervention using standardized patients (SPs) trained to improve residents' detection and advising of problem drinkers. DESIGN: Pretest‐posttest design assessing resident behavior and skills. SUBJECTS: Nineteen internal medicine residents in a University Hospital General Internal Medicine Clinic. INTERVENTION: Announced SPs were interviewed by residents and presented to faculty who provided brief instruction on the National Institute on Alcohol Abuse and Alcoholism g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…[9][10][11] In the medical education field there have been several controlled trials, as well as uncontrolled studies, that have shown that BAI training can be effective in improving physician knowledge and skills to address alcohol use. [12][13][14][15][16][17] One randomized trial demonstrated that BAI-trained physicians and health care providers used more BAI components on hazardous drinking patients when encouraged and supported to do so by a primary care office system. 16 In most of this research, providers knew that their clinical skills were being assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] In the medical education field there have been several controlled trials, as well as uncontrolled studies, that have shown that BAI training can be effective in improving physician knowledge and skills to address alcohol use. [12][13][14][15][16][17] One randomized trial demonstrated that BAI-trained physicians and health care providers used more BAI components on hazardous drinking patients when encouraged and supported to do so by a primary care office system. 16 In most of this research, providers knew that their clinical skills were being assessed.…”
Section: Introductionmentioning
confidence: 99%
“…In the only study to date in which participants were blinded to the overall aim of improving frequency of BAI being conducted after training, a control group was lacking. 14 This presented a significant risk of not identifying confounding variables that could have impacted on the performance of the residents. The present research assessed the performance of residents trained in BAI.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wilk and Jensen (2002) concluded that even a single 1-hour training session with SPs enhanced the education of medical residents learning how to detect potential alcoholism in patients. Ryan et al (2010) reported that the use of SPs in a comparatively limited capacity was an effective component of teaching communication skills to medical and nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…Research has included psychiatric and mental health training (Eagles, Calder, Wilson, Murdoch, & Sclare, 2007;Hanson et al, 2008;Lewy, Sells, Gilhooly, & McKelvey, 2009;Wissow et al, 2008;Yudkowsky, 2002), psychotherapy education (Brown, 2008;Lewis, 2002;McNaughton, Ravitz, Wadell, & Hodges, 2008), and substance abuse (Parish, Ramaswamy, Stein, Kachur, & Arnsten, 2006;Wilk & Jensen, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…20,38 Educational efforts during residency should include instruction on NIAAA screening guidelines as this method has been validated, 39 and familiarity with these guidelines correlated with favorable practices in a national survey of practicing primary care physicians. 26 Furthermore, incorporating instruction on NIAAA guidelines into residency education has been shown to improve screening and intervention practices, 40 and an instruction manual has been developed to aid in the implementation of this training. 41 Patient self-administered screening questions can aid in recognizing alcohol abuse.…”
Section: Journal Of Addictive Diseasesmentioning
confidence: 99%